Baicalein inhibits NLRP3 inflammasome activation and mitigates placental inflammation and oxidative stress in gestational diabetes mellitus - Yao Jun; Pan Jiaying; Jiang Qiaoying; Wang Hui; Zhao Yiqi (Open Life Sciences)
Gestational diabetes mellitus (GDM) is a common metabolic disorder during pregnancy characterized by glucose intolerance, which poses risks to both maternal and fetal health. Baicalein, a flavonoid derived from the roots of Scutellaria baicalensis Georgi, exhibits various biological functions and has been implicated in the modulation of several diseases. However, the regulatory effects and underlying mechanisms of Baicalein in GDM progression remain unclear. In this study, we found that Baicalein ameliorates metabolic disturbances in GDM mice by improving glucose tolerance, insulin sensitivity, fasting blood glucose levels, and plasma insulin levels. Additionally, Baicalein treatment positively impacted litter size and birth weight. GDM mice exhibited increased inflammation and oxidative stress, which were mitigated following Baicalein administration (40 mg/kg). Furthermore, elevated protein levels of NLRP3, IL-1β, and IL-18 observed in GDM mice were reduced by Baicalein treatment. In conclusion, Baicalein inhibits the NLRP3 inflammasome and alleviates placental inflammation and oxidative stress associated with GDM. These findings provide valuable insights into the potential therapeutic role of Baicalein in managing GDM.